Are Microcredit Borrowers in Bangladesh Over-indebted ? - Khandker, Shahidur R.; Faruqee, Rashid; Samad, Hussain A. (World Bank, Washington, DC, 2013)
Microcredit programs in Bangladesh have experienced spectacular growth in recent years, with a growing number of borrowers availing credit from multiple microcredit agencies. There is a growing concern that if there are not sufficient returns to borrowing from microfinance institutions (MFIS), some borrowers might be taking loans that they will not be able to repay. A household may be considered over-indebted, for example, if its debt liability exceeds 40 percent of its income or assets. Using a long panel of household survey data from Bangladesh, the paper finds that some 26 percent of microcredit borrowers are over-indebted on this measure versus 22 percent of non-microcredit borrowers. Econometric analysis suggests that both MFI competition and multiple borrowing raise indebtedness. However, repeated borrowing, while it affects short-term liability adversely, does affect the long-term debt-asset ratio favorably. That is, repeated borrowing helps increase assets more than debt over time. Microcredit borrowers in Bangladesh are thus not necessarily over-indebted. But when borrowing is seen as protection against shocks such as floods even at the cost of being indebted, MFIs may offer micro-insurance schemes to safeguard borrowers against economic shocks.